Intermuscular lipoma of the submandibular space - Adachi, Patrícia; Kaba, Shajadi P.; Soubhia, Ana Maria Pires [UNESP]; Shinohara, Elio Hitoshi [UNESP] (My University, 2011)
Deep lipomas, especially in the head and neck region, are uncommon. This report describes the case of a patient with a large intermuscular lipoma of the submandibular space, which had been present for 10 years and was diagnosed by computed tomography. The clinical, imaging, and histopathological features, as well as the management of the tumor, are described.
Keywords: Computed tomography; intermuscular lipoma; submandibular space; adipocyte; case report; computer assisted tomography; fine needle aspiration biopsy; follow up; human; lipoma; male; middle aged; muscle tumor; neck muscle; pathology; Adipocytes; Biopsy, Fine-Needle; Follow-Up Studies; Humans; Lipoma; Male; Middle Aged; Muscle Neoplasms; Neck Muscles; Tomography, X-Ray Computed